EVALUASI PROGRAM GERAKAN LITERASI SEKOLAH (GLS) DI SMP NEGERI 17 MATARAM - Yusuf, Yusuf; Wahab Jufri, A. (Berajah Journal, 2023)
Evaluation of the implementation of the literacy program at SMPN 17 Mataram as a whole is quite good in terms of the evaluation results of the program context based on Permendiknas Number 23 of 2015 and the background of the program has been understood by TLS, students, teacher boards, and student's parents. The program input as a whole is quite good, as seen from the results of the program evaluation, namely at the program development stage which refers to Permendiknas Number 23 of 2015 which was then developed independently by SMPN 17 Mataram in the form of a School Literacy Movement Guide. The overall process is quite good, seen from the results of the evaluation of the program process, namely the time and place for implementing the literacy program, the scope of the program, the role of partners for students, program services, activity journals, program obstacles, monitoring of accompanying teachers, and program supervision from the head of the madrasa and program partners. The overall results are quite good and show the success of the program, seen from the results of product evaluation (results), namely the conformity of targets and program results, changes in student behavior in reading, increasing learning outcomes and student achievement which can be seen from academic changes in the form of exam results which continues to increase.